2-absorbing and weakly 2-absorbing elements in multiplicative lattices - TEKİR, ÜNSAL (TAYLOR & FRANCIS INC, 2014)
In this article we study weakly 2-absorbing elements and 2-absorbing elements in C-lattices. Next we characterize C-lattices in which every nonzero proper element is a (weakly) 2-absorbing element. We also establish a new characterization for principal element domains in terms of 2-absorbing elements.
Keywords: 2-Absorbing element; Principal element lattice; Principal element; Prufer lattice; Regular lattice; Weakly 2-absorbing element; Primary 06F10; Secondary 06F05; 13A15; COMMUTATIVE RINGS; IDEALS